The Strategy Of Defense Diplomacy In Strengthening Pancasila In Facing Transnational Islamic Ideology - Rodon Pedrason (Syntax Corporation, 2022)
The diversity of ethnicity, culture, ethnicity, religion, and race makes Indonesia vulnerable to conflict. Thus, a strategy is needed to minimize conflicts in Indonesia. This study aims to examine the defense diplomacy strategy in more depth in strengthening Pancasila in the face of transnational Islamic ideology. This study uses a qualitative approach. Data was collected using FGD, interviews, and document analysis. Data analysis used thematic analysis. The results of this study indicate that Indonesia needs to create a Pancasila diplomacy strategy. Pancasila diplomacy is Indonesia's diplomatic strategy to achieve national interests in the form of people's unity, the integrity of the Republic of Indonesia, and the nation's safety from the threat of transnational Islamic ideology. Pancasila diplomacy has three fundamental interests: absolute, urgent, and defense cooperation. The implication of this research is to support the government, especially the ministry of defense, in countering transnational Islam, facing the threat of terrorism, countering threats to national ideology, and creating global peace.